A two-stage bait-trap method for collecting live subterranean termites under tropical field conditions - AMADEUS CLEAVER CHANDRA; HENDRA KURNIAWAN MAURY; INTAN AHMAD (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Chandra AC, Maury HK, Ahmad I. 2026. A two-stage bait-trap method for collecting live subterranean termites under tropical field conditions. Biodiversitas 27 (6): d270612. https://doi.org/10.13057/biodiv/d270612. Obtaining sufficient numbers of live subterranean termites for laboratory-based research is a persistent methodological challenge. Conventional collection methods, including soil excavation, mound destruction, and log dismantling, are labor-intensive and destructive. This study introduces and evaluates a two-stage bait-trap method for collecting live subterranean termites from active colonies under tropical field conditions while minimizing disturbance to the substrate. In the first stage, wooden stakes were installed as bait stations to locate active termite foraging sites. In the second stage, sandwich (stacked-board) traps constructed from the same wood species were installed over infested stakes. Three locally available timber species, rubberwood (Hevea brasiliensis), acacia (Acacia mangium), and jabon (Anthocephalus cadamba) were used as bait materials, with 22 stakes per species evaluated during a three-month field trial, including one month of trap deployment. A total of 33 sandwich traps were installed following initial stake infestation; overall harvest success (initial termite encounter) was 70% (23 of 33), and active-capture success (live termites present at retrieval) was 48% of harvested traps (11 of 23). These two outcomes represent distinct endpoints: encounter and sustained live capture. Mean termite yield across all active traps was 944±854 individuals, including workers and soldiers. No statistically significant difference in termite counts was detected among wood species (F₂,₈: 0.74, p: 0.507; n: 11 active traps); the analysis was underpowered for detecting small-to-moderate effects. Three termite genera were recovered: Coptotermes, Microtermes, and Nasutitermes. The two-stage method successfully demonstrated live termite collection under tropical field conditions at the study site and offers a promising field protocol with potential applications in biodiversity surveys, ecological studies, and toxicological research that require live specimens. Further validation across additional sites and seasons is needed before the method can be considered broadly standardized.